2015
DOI: 10.1021/acs.jchemed.5b00294
|View full text |Cite
|
Sign up to set email alerts
|

Student Perceptions of Online Homework Use for Formative Assessment of Learning in Organic Chemistry

Abstract: Use of online homework as a formative assessment tool for organic chemistry coursework was examined. Student perceptions of online homework in terms of (i) its ranking relative to other course aspects, (ii) their learning of organic chemistry, and (iii) whether it improved their study habits and how students used it as a learning tool were investigated. Our students perceived the online homework as one of the more useful course aspects for learning organic chemistry content. We found a moderate and statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 33 publications
(119 reference statements)
4
39
0
Order By: Relevance
“…The computer‐based, pre‐test, assessment was accessed by over 300 students, who rated it positively on a Likert‐type agreement scale regarding the use of computer‐based‐assessments, the ease of use, importance and whether these types of assessments objectively reflect a students' performance. Similarly, Richards‐Babb et al () found that students strongly agreed that use of OFAs in a Chemistry course encouraged more consistent studying habits and agreed that they crammed for tests less.…”
Section: Benefits Of Online Formative Assessmentmentioning
confidence: 94%
See 2 more Smart Citations
“…The computer‐based, pre‐test, assessment was accessed by over 300 students, who rated it positively on a Likert‐type agreement scale regarding the use of computer‐based‐assessments, the ease of use, importance and whether these types of assessments objectively reflect a students' performance. Similarly, Richards‐Babb et al () found that students strongly agreed that use of OFAs in a Chemistry course encouraged more consistent studying habits and agreed that they crammed for tests less.…”
Section: Benefits Of Online Formative Assessmentmentioning
confidence: 94%
“…Students developed their academic self‐regulation through this learning process: taking the OFA, receiving feedback in the form of a score, reflecting on that feedback, using this feedback to target certain content areas for more extensive review, then taking the actual exam having gone through this self‐reflective process (Deutsch et al, ; Richards‐Babb et al, ). These types of OFAs provided students with the opportunity to practice their performance, to reflect upon the outcomes, to self‐evaluate their learning and then use that information to improve their studying habits using strategic practice (Zimmerman, ).…”
Section: Benefits Of Online Formative Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Online tutorials have been used in postsecondary organic chemistry courses. 41,42 Richards-Babb et al implemented online, targeted assessments as a formative tool to increase learning in an organic chemistry course; the authors found that their students felt that the tool was useful. Additionally, performance on the assessments correlated with the students' final grades in the course.…”
Section: Online Tutorialsmentioning
confidence: 99%
“…Additionally, performance on the assessments correlated with the students' final grades in the course. 41 O'Sullivan and Hargaden developed tutorials in their organic chemistry course that prompted students to draw chemical structures (i.e., predict the products and synthesis problems) and the system then provided targeted feedback on their structures. 42 Overall, students agreed that the tutorials were a "beneficial learning experience".…”
Section: Online Tutorialsmentioning
confidence: 99%